The need to preserve surgical training. Issue 2 (26th December 2020) - Masterton, Gary
Abstract : Surgical trainees have found their training opportunities disrupted throughout the COVID-19 pandemic. With an uncertain future and potential impeding second wave considerations should be made on how surgical training can be preserved.